2013
DOI: 10.1074/jbc.m112.447243
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin Regulates Transforming Growth Factor-β-stimulated Extracellular Matrix Production

Abstract: Background: Endoplasmic reticulum (ER) stress is associated with fibrotic diseases, although the mechanisms are not completely understood. Results: The ER stress protein calreticulin regulates TGF-␤ stimulated extracellular matrix through control of intracellular calcium and NFAT signaling. Conclusion: Calreticulin is necessary for TGF-␤ stimulated extracellular matrix production. Significance: These findings identify calreticulin as a mechanistic link between ER stress and fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 88 publications
4
81
0
Order By: Relevance
“…The direct profibrotic role of UPR mediators in activation of TGF-β signaling in lung fibroblasts could also be proven by a study from Zimmerman and coworkers who showed that the ER chaperone calreticulin is required for TGF-β induced expression of Col1a1 and Fn, whereas knockout of Calr resulted in abrogation of cellular responsiveness to TGF-β even in the presence of active Smad 2/3 signaling [233]. Importantly, calreticulin was required for TGF-β induced ECM synthesis under conditions of ER stress, as tunicamycin-induced ER stress was insufficient to induce ECM production in TGF-β stimulated Calr (-/-) MEFs (but induced ECM production in TGF-β stimulated Calr (+/+) wt-MEFs, due to upregulation of Calr in response to ER stress) [233]. Taken together, all these results point out that selected protective UPR pathways are involved in fibroproliferative remodeling that are independent of severe ER stress and apoptosis [232,233,238].…”
Section: Adaptive Er Stress In Mesenchymal Cells Of Ipf Lungsmentioning
confidence: 89%
See 4 more Smart Citations
“…The direct profibrotic role of UPR mediators in activation of TGF-β signaling in lung fibroblasts could also be proven by a study from Zimmerman and coworkers who showed that the ER chaperone calreticulin is required for TGF-β induced expression of Col1a1 and Fn, whereas knockout of Calr resulted in abrogation of cellular responsiveness to TGF-β even in the presence of active Smad 2/3 signaling [233]. Importantly, calreticulin was required for TGF-β induced ECM synthesis under conditions of ER stress, as tunicamycin-induced ER stress was insufficient to induce ECM production in TGF-β stimulated Calr (-/-) MEFs (but induced ECM production in TGF-β stimulated Calr (+/+) wt-MEFs, due to upregulation of Calr in response to ER stress) [233]. Taken together, all these results point out that selected protective UPR pathways are involved in fibroproliferative remodeling that are independent of severe ER stress and apoptosis [232,233,238].…”
Section: Adaptive Er Stress In Mesenchymal Cells Of Ipf Lungsmentioning
confidence: 89%
“…Taken together, the results by Semren et al suggest that myofibroblasts use increased ERAD function as shown by elevated 26S proteasomal activity in order to maintain ER homeostasis and cell survival in response to TGF-β-mediated elevation of ECM protein-production [238]. The direct profibrotic role of UPR mediators in activation of TGF-β signaling in lung fibroblasts could also be proven by a study from Zimmerman and coworkers who showed that the ER chaperone calreticulin is required for TGF-β induced expression of Col1a1 and Fn, whereas knockout of Calr resulted in abrogation of cellular responsiveness to TGF-β even in the presence of active Smad 2/3 signaling [233]. Importantly, calreticulin was required for TGF-β induced ECM synthesis under conditions of ER stress, as tunicamycin-induced ER stress was insufficient to induce ECM production in TGF-β stimulated Calr (-/-) MEFs (but induced ECM production in TGF-β stimulated Calr (+/+) wt-MEFs, due to upregulation of Calr in response to ER stress) [233].…”
Section: Adaptive Er Stress In Mesenchymal Cells Of Ipf Lungsmentioning
confidence: 95%
See 3 more Smart Citations